2018
DOI: 10.3389/fnins.2018.00693
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Treatment Approaches for Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease, manifesting as a characteristic movement disorder with a number of additional non-motor features. The pathological hallmark of PD is the presence of intra-neuronal aggregates of α-synuclein (Lewy bodies). The movement disorder of PD occurs largely due to loss of dopaminergic neurons of the substantia nigra, resulting in striatal dopamine depletion. There are currently no proven disease modifying treatments for PD, with management opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 105 publications
1
104
0
1
Order By: Relevance
“…Moreover, polyphenols like ferulic acid are effective scavengers for free radicals and superoxide anions and are used to prevent lipid peroxidation as food additives (Srinivasan et al, 2007). Although there is an ongoing search for improved PD therapeutics which can halt or reverse the disease progression rather than treat the symptoms, the complicated mechanism of PD challenges the development of effective therapeutics focused on unitary targets (Stoker et al, 2018). A multi-target therapeutic approach that can modulate more than one pathological feature may be more promising than single-target therapeutics to slow or halt disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polyphenols like ferulic acid are effective scavengers for free radicals and superoxide anions and are used to prevent lipid peroxidation as food additives (Srinivasan et al, 2007). Although there is an ongoing search for improved PD therapeutics which can halt or reverse the disease progression rather than treat the symptoms, the complicated mechanism of PD challenges the development of effective therapeutics focused on unitary targets (Stoker et al, 2018). A multi-target therapeutic approach that can modulate more than one pathological feature may be more promising than single-target therapeutics to slow or halt disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…49 However, these grafts did not demonstrate the same potential to restore the dopamine levels in the striatum and ameliorate behavioral deficits as the fetal grafts in preclinical studies; therefore, it was not surprising that clinical trials evaluating non-neuronal cell sources did not result in significant motor improvements compared with the relatively successful human fetal ventral mesencephalic grafts. 66 These experiments illustrate the importance of validating potential grafting strategies by demonstrating robust cell survival, host integration, and dopamine release in animal models before clinical trials.…”
Section: Regenerative Medicinementioning
confidence: 95%
“…47,48 Moreover, several grafting strategies using different dopamine-producing tissues have been evaluated in clinical trials, such as adrenal medullary cells (AMCs), sympathetic ganglia, carotid body cells, retinal pigmentary epithelial cells linked to microcarriers, and porcine ventral mesencephalon tissue. 66 However, the most-effective transplantation strategy has been with human fetal mesencephalic tissue. Preclinical rodent studies have shown that transplanted dopaminergic neurons from human fetal mesencephalic grafts can innervate the dopamine-deprived striatum, receive inputs from host neurons, and diminish rotational behavioral symptoms.…”
Section: Regenerative Medicinementioning
confidence: 99%
“…The movement disorder known as Parkinson's disease (PD), the second most common neurodegenerative disorder, occurs largely due to the loss of dopaminergic neurons of the substantia nigra, resulting in striatal depletion of neurotransmitter dopamine. AAV-based gene therapy vectors could be effectively used for gene therapy of Parkinson's disease (PD) through increasing dopamine levels in target cells [115]. Another strategy proposed for gene therapy of PD is based on targeting of neural parenchyma by AAV-based α-synuclein expression vector (AAV-PHP.B-GBA1) delivered via an iv administration, as opposed to commonly used injection of the mouse forebrain.…”
Section: Aav-based Gene Therapy For Parkinson's Diseasementioning
confidence: 99%